FEASIBILITY STUDY OF JUST IN TIME INVENTORY MANAGEMENT ON CONSTRUCTION PROJECT - MR. PATIL YOGENDRA R. (International Journal of Innovations in Engineering Research and Technology, 2021)
Just in time philosophy has lot of Potentional for managing movement of construction material from manufacturing yard to construction site. The traditional approach to material delivery has been used in construction industry for many years. It is imbedded in the corporate structure as the way to procure materials. Major Construction Industries have been trying to adopt new business initiatives in order to stay alive in the new competitive market place. Companies must strive to create high quality, and Low cost products that can get to the customers in the shortest time possible. Just-in-time production system is one of these initiatives that focus on cost reduction by eliminating non-value added activities. This Paper Deals with Implementing Just in TimeInventory Control Approach on Highway Construction. JIT has Tremendous Effect on Material Delivery Operation. During implementation of JIT organization is required to put desired efforts on all levels of the work.